Digital Innovation and Supply Chain Performance: Investigating the Moderating Effect of Technology Usage on Risk Management-Resilience-Performance Linkages - Lei , Mingyu; Zakuan, Norhayati; Hasan, Mohd Zulfabli; Mat Saman, Muhamad Zameri; Chen, Xin (Digital Technologies Research and Applications, 2026)
This study aims to investigate the interrelations among digital innovation, risk management, resilience, and performance in supply chain contexts, in which technology utilization is conceptualized as a moderator. Based on the concepts of dynamic capabilities and the resource-based view, the proposed model suggests risk management and resilience as sequential mediators between digital innovation and performance. The model is empirically validated using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a sample of 256 manufacturing and service organizations selected from the World Bank Enterprise Surveys dataset. Findings show that digital innovation has both direct (β = 0.218) and indirect effects on supply chain performance through risk management and resilience. Digital innovation exhibits the strongest association with supply chain risk management (β = 0.521), followed by risk management's effect on resilience (β = 0.489) and resilience's effect on performance (β = 0.372). Technology usage strengthens both the risk management–resilience path (β = 0.127) and the resilience–performance path (β = 0.143). Sequential mediation accounts for 53.3% of the total effect, as measured by the Variance Accounted For (VAF) index, confirming partial mediation. This study also contributes to the supply chain management literature by providing empirical specification for the integrated paths in which digital innovation drives performance through risk management and resilience capabilities, and technology application as a boundary condition in these paths. The results indicate that supply chain managers should integrate digital innovation investments with risk management and resilience capabilities for the best performance in supply chain management.